BUILDING UNDERSTANDING AND AWARENESS OF ENVIRONMENTAL POLLUTION THROUGH COMIC (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
Environmental problems such as widespread pollution are ongoing threats to the livelihood of the current and future generations. Engaging learning media such as comics can be used to instill the importance of understanding our role in solving environmental pollution problems. This paper reports the promising benefit of using comics in building junior high school students understanding and awareness of water, soil, dan air pollution. Comic is a visual medium, and whether students’ specific learning preferences play a role in learning results was also determined and discussed. Masalah lingkungan seperti pencemaran merupakan ancaman berkelanjutan bagi kehidupan generasi saat ini serta generasi mendatang. Media pembelajaran yang menarik seperti komik dapat digunakan untuk menanamkan pentingnya memahami peran kita dalam menyelesaikan masalah pencemaran lingkungan. Artikel ini melaporkan manfaat yang menjanjikan dari penggunaan komik dalam membangun pemahaman dan kesadaran siswa sekolah menengah pertama tentang pencemaran air, tanah, dan udara. Komik adalah media visual, dan apakah gaya belajar siswa berperan dalam hasil belajar juga diukur dan didiskusikan.
Keywords: comic; environment awareness; environmental pollution; learning preferences; komik; kesadaran lingkungan; polusi lingkungan; gaya belajar